Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1080/02614367.2011.552623
|View full text |Cite
|
Sign up to set email alerts
|

Centre‐based and expedition‐based (wilderness) adventure experiential learning regarding personal effectiveness: an explorative enquiry

Abstract: The purpose of this study is to compare a centre-based adventure programme (CBAP) with an expedition-based wilderness programme (EBWP) with regard to personal effectiveness. In comparing these two programmes, this study made use of a crossover research design with data collection according to DE Vos. Participants were 28 third-year students (14 men and 14 women), aged 20 to 23 ( = 21.6 ± 0.7) from the Northwest University (Potchefstroom Campus) in South Africa. Both interviews and questionnaires (n = 28) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
14
0
2
Order By: Relevance
“…observed that higher active outdoor play was associated with better self-regulation and in turn with better academic achievement among pre-school children [ 138 ]. Others have shown similar psychological benefits of active outdoor play [ 139 , 140 , 141 , 142 ].…”
Section: Resultsmentioning
confidence: 93%
“…observed that higher active outdoor play was associated with better self-regulation and in turn with better academic achievement among pre-school children [ 138 ]. Others have shown similar psychological benefits of active outdoor play [ 139 , 140 , 141 , 142 ].…”
Section: Resultsmentioning
confidence: 93%
“…It adds something different and special to the achievement. Interestingly, Greffrath et al (2013) found that a centre-based adventure program improved communication abilities, productiveness and competition within the group more than an expedition based wilderness programme, except that 'group morale' was in favour of the expedition-based wilderness program, which showed a medium effect (d = 0.5).…”
Section: Post-expedition Feedback Datamentioning
confidence: 99%
“…For the improvement of personal effectiveness, an expedition based wilderness programme seemed to be of relatively more value (mainly on account of the impact of the wilderness environment) than a centre based adventure programme (Greffrath et al, 2011). On the basis of comments in the interviews, it may be interpreted that having time to learn at their own pace, to talk with other people, to see other people being productive (sometimes with the support and encouragement of their fire leaders) and to wild camp are the result of modern life denying young people uncluttered time and space to think, reflect, talk and observe, and the expedition created these spaces which the young people found both unusual and valuable (Allison, 1998).…”
Section: Post-expedition Feedback Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive shortterm study abroad of two weeks or less includes adventure travel and has been found to result in similar or stronger educational and personal impacts on participants (Alexander, Bakir & Wickens, 2010). Expedition-based learning specifically has been shown to significantly increase measurable personal abilities, organizational skills, overall effectiveness, stress management, openness in thinking, time efficiency, and coping with change (Greffath, Meyer, Strydom & Ellis, 2011). The opportunities for growth generally benefit all students, regardless of income, although most international study travel participants are wealthy (Lewin, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%